2017
DOI: 10.3847/2041-8213/aa71b5
|View full text |Cite
|
Sign up to set email alerts
|

ALMA Discovery of Solar Umbral Brightness Enhancement at λ = 3 mm

Abstract: We report the discovery of a brightness enhancement in the center of a large sunspot umbra at a wavelength of 3 mm using the Atacama Large Millimeter/sub-millimeter Array (ALMA). Sunspots are amongst the most prominent features on the solar surface, but many of their aspects are surprisingly poorly understood. We analyzed a λ=3 mm (100 GHz) mosaic image obtained by ALMA, which includes a large sunspot within the active region AR12470 on December 16, 2015. The 3 mm map has a 300"×300" field-of-view and 4".9×2".… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 26 publications
1
17
0
Order By: Relevance
“…Indeed, Iwai & Shimojo (2015) used the 45 m Nobeyama telescope to determine the temperature of the umbra and penumbra at 85 and 115 GHz and also reported finding an umbra cooler than the quiet Sun. These findings were recently confirmed by Loukitcheva et al (2017) and Iwai et al (2017), using the images obtained with the Atacama Large Millimeter Array (ALMA) with a synthesized beam of 0.5 arcsec at frequencies of 100 (λ = 3.0 mm) and 239 GHz (λ = 1.2 mm). With lower spatial resolution, Silva et al (2005) analyzed ARs during 23 days at 212 (λ = 1.4 mm) and 405 GHz (λ = 0.7 mm) with the Solar Submillimeter Telescope, adding complementary data from NoRH at 17 and 34 GHz (λ = 8.8 mm).…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…Indeed, Iwai & Shimojo (2015) used the 45 m Nobeyama telescope to determine the temperature of the umbra and penumbra at 85 and 115 GHz and also reported finding an umbra cooler than the quiet Sun. These findings were recently confirmed by Loukitcheva et al (2017) and Iwai et al (2017), using the images obtained with the Atacama Large Millimeter Array (ALMA) with a synthesized beam of 0.5 arcsec at frequencies of 100 (λ = 3.0 mm) and 239 GHz (λ = 1.2 mm). With lower spatial resolution, Silva et al (2005) analyzed ARs during 23 days at 212 (λ = 1.4 mm) and 405 GHz (λ = 0.7 mm) with the Solar Submillimeter Telescope, adding complementary data from NoRH at 17 and 34 GHz (λ = 8.8 mm).…”
Section: Introductionmentioning
confidence: 61%
“…Previous works with better spatial resolution have shown that at submillimeter wavelengths the sunspot umbra is cooler than the quiet Sun, while the penumbra has a similar temperature and the surrounding plage is much hotter (Lindsey & Kopp 1995;Loukitcheva et al 2017;Iwai et al 2017). However, SST beam sizes, which are of the same order of the AR, cannot resolve these spatial variations and ∆T b is an average over the whole region, with the penumbra and surrounding plages dominating the emission, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The ALMA dataset we used was provided by the ALMA observatory as part of its Science Verification data release. Previous publications based on this ALMA data release are Bastian et al (2017), Iwai et al (2017), Loukitcheva et al (2017), andShimojo et al (2017). Only Shimojo et al (2017) used data from the same day (2015 December 17) as considered here, and that study was focused on a small brightening rather than the sunspot itself.…”
Section: Observationsmentioning
confidence: 99%
“…In Loukitcheva et al (2017) the study of Iwai et al (2017) was extended by analyzing the observations of the same sunspot at a wavelength of 1.3 mm, and by comparing ALMA observations at the two wavelengths with the predictions of sunspot umbral, and for the first time, penumbral models. The umbra was found to look very different at λ = 1.3 mm from its image at 3 mm.…”
Section: First Solar Alma Sciencementioning
confidence: 99%
“…While current capabilities of solar Figure 6: IRIS slit-jaw images of AR12470 at (a) 1330Å and (b) 1400Å, with the overlaid color contours corresponding to the brightness temperature levels in the 3 mm-λ map at 6300 K (purple), 6900 K (blue), 7500 K (green), 8100 K (orange), and 8700 K (red). From Iwai et al (2017). c AAS.…”
Section: Conlusionsmentioning
confidence: 99%